Adhesive Catalyst Immobilization of Palladium Nanoparticles on Cotton and Filter Paper: Applications to Reusable Catalysts for Sequential Catalytic Reactions. Issue 5 (11th March 2014) - Nishikata, Takashi; Tsutsumi, Hironori; Gao, Lei; Kojima, Keisuke; Chikama, Katsumi; Nagashima, Hideo
Abstract Palladium nanoparticles dispersed in ammonium salts of hyperbranched polystyrenes are adhesively immobilized on the surface of cotton or filter papers by simply heating with dicarboxylic acids or halide anions. The resulting Pd@cotton and Pd@filter paper behave as reusable catalysts; in particular, Pd@filter paper is useful as catalyst for application to sequential cross‐coupling and hydrogenation reactions to produce several different products with just one piece of the paper catalyst. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>